Analisis Penerapan Prinsip Ekowisata di Desa Wisata Sade dan Tetebatu: Sebuah Studi Perbandingan - M. Farfan; Rahmad Hidayat; Asfarony Hendra Nazwin (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
Indonesia, with its abundant natural and cultural wealth, has great potential for ecotourism development. Sade and Tetebatu villages in West Nusa Tenggara are examples of ecotourism implementation with different characteristics. This study aims to identify how ecotourism principles are applied in both villages and to compare their strengths and weaknesses. The research method used is qualitative with a descriptive approach, through observation, interviews, and documentation. The results show that the implementation of ecotourism principles in Sade and Tetebatu consistently involves six key aspects: nature conservation, cultural appreciation, community participation, environmental education, economic empowerment, and sustainability. The difference lies in the approach: Sade emphasizes the preservation of Sasak culture, while Tetebatu focuses on nature conservation and the use of environmentally friendly technology. Local characteristics are determining factors that influence the practice of ecotourism in both villages. The conclusion of this study is that the application of ecotourism principles in Sade and Tetebatu can serve as a model for sustainable tourism development that provides real benefits to local communities while preserving culture and the environment.